The Think Pair Share Cooperative Learning Model Assisted by Children's Story Text Improves Speaking Skills - Ni Made Nila Pramesti; Maria Goreti Rini Kristiantari (Universitas Pendidikan Ganesha, 2023)
The learning model the teacher uses needs to be more diverse and more able to accommodate the development of speaking skills. It causes students' speaking skills not to develop optimally. This study aims to analyze the effect of the think pair share cooperative learning model assisted by children's story texts on speaking skills in fourth-grade elementary school students. This study used a quasi-experimental design with a non-equivalent control group design. The population in the study were all fourth-grade elementary school students consisting of 11 fourth-grade students with 340 students. The data collection method uses the non-test method in the form of an observation sheet. The technique used is descriptive statistical analysis and inferential statistics. The results of testing the hypothesis showed a significant difference between students taught with the cooperative model of the think pair share type assisted by children's story text and students taught with conventional learning models. The cooperative model of the think pair share type influences the speaking skills of fourth-grade elementary school students. It was concluded that the cooperative model of the think pair share type can improve speaking skills in fourth-grade elementary school students.